The relative contribution of physical fitness to the technical execution score in youth rhythmic gymnastics - Donti, O.; Bogdanis, G. C.; Kritikou, M.; Donti, A.; Theodorakou, K. (Journal of Human Kinetics, 2016)
This study examined the association between physical fitness and a technical execution score in rhythmic gymnasts varying in the performance level. Forty-six young rhythmic gymnasts (age: 9.9 ±1.3 years) were divided into two groups (qualifiers, n=24 and non-qualifiers, n=22) based on the results of the National Championships. Gymnasts underwent a series of physical fitness tests and technical execution was evaluated in a routine without apparatus. There were significant differences between qualifiers and non-qualifiers in the technical execution score (p=0.01, d=1.0), shoulder flexion (p=0.01, d=0.8), straight leg raise (p=0.004, d=0.9), sideways leg extension (p=0.002, d=0.9) and body fat (p=.021, d=0.7), but no differences were found in muscular endurance and jumping performance. The technical execution score for the non-qualifiers was significantly correlated with shoulder extension (r=0.423, p<0.05), sideways leg extension (r=0.687, p<0.01), push ups (r=0.437, p<0.05) and body fat (r=0.642, p<0.01), while there was only one significant correlation with sideways leg extension (r=0.467, p<0.05) for the qualifiers. Multiple regression analysis revealed that sideways leg extension, body fat, and push ups accounted for a large part (62.9%) of the variance in the technical execution score for the non-qualifiers, while for the qualifiers, only 37.3% of the variance in the technical execution score was accounted for by sideways leg extension and spine flexibility. In conclusion, flexibility and body composition can effectively discriminate between qualifiers and non-qualifiers in youth rhythmic gymnastics. At the lower level of performance (non-qualifiers), physical fitness seems to have a greater effect on the technical execution score.